A Comprehensive Review on Analytical Method Development using RP-HPLC and Recent Advances in Pharmaceutical Applications - Kumar, Deepak; Kumar, Amrendra; Kumar, Vinay; Raj, Arjesh; Rai, Raja Ram Mohan; Baliyan, Vishal; Kumar, Nitish (Journal for Research in Applied Sciences and Biotechnology, 2023)
The analytical technique of choice for separating, identifying, and quantifying complex mixtures is high-performance liquid chromatography (HPLC). Reverse-phase liquid chromatography (RP-HPLC) is the preferred separation mode for high-performance liquid chromatography (HPLC) due to its adaptability and higher selectivity for hydrophobic compounds. This review article discusses the fundamentals of reversed-phase high-performance liquid chromatography (RP-HPLC). This covers the separation principle, various stationary and mobile phase types, and separation-affecting variables. This article highlights the need of developing and testing such methods in addition to outlining the advantages of using RP-HPLC in industries like pharmaceutical, food, and environmental analysis. As examples of more recent advancements in RP-HPLC, new stationary and mobile phases, RP-HPLC downsizing, and hyphenated methods are also discussed. This review article provides a comprehensive tool for designing, refining, and validating RP-HPLC processes.